1,4-Bis(2-((1R,5S)-6,6-dimethylbicyclo[3.1.1]hept-2-en-2-yl)ethyl)piperazine - Nikolai S. Li-Zhulanov; Artem D. Rogachev; Yuri V. Gatilov; Konstantin P. Volcho; Nariman F. Salakhutdinov (Molbank, 2024)
The reaction of (−)-nopol mesylate with piperazine in acetonitrile under reflux, afforded symmetric 1,4-bis(2-((1R,5S)-6,6-dimethylbicyclo[3.1.1]hept-2-en-2-yl)ethyl)piperazine in a good yield. The compound was fully characterized and its structure was confirmed using X-ray diffraction analysis.